Rancang Bangun Akuaponik untuk Masyarakat Kelapa Dua Tangerang - Soewono, Arka; Iskandar, Isdaryanto; Hutagalung, Rory Anthony; Fretes, Anthon de; Darmawan, Canisius Ivan (Program Studi Teknik Industri, Fakultas Teknik, Universitas Katolik Indonesia Atma Jaya Jakarta, 2021)
Aquaponic is a combination hydroponic (cultivation of plants without soil) and aquaculture (fish growing) that promotes sustainable food production. In order to be adopted by general population, the design of aquaponics needs to be practical and economical. The main purpose of this community outreach is to design and introduce small-scale aquaponics system that can be used by homeowners with limited backyard. For this purpose, the community located at Kelapa Dua Tangerang was chosen as the main partner. The prototype of the small-scale aquaponics was then used as education and demonstration tool to encourage the community of Kelapa Dua Tangerang to adopt eco-friendly aquaponics cultivation system. The prototype of the aquaponics worked flawlessly with the water circulation inside the system was set at 0.046 litre/second. The water was used to supply adequate nutriens for water spinach, lettuce and pak choy which can be harvested in two months. In addition, this leafy greens can enhance the overall yard aesthetics. For the aquaculture, the catfish in the tank showed steady grow rate and healthy condition. In general, the education process can be considered successful as indicated by positive responses from the community (feedback score of 2.93 out of 4). From joint evaluation, the community excited with further development of the small-scale aquaponics.